Wood Carving in the Interior - Khakberdiyev Alikhuja Muratovich (Researchparks Publishing, 2022)
Wood is a wonderful natural material from which you can create decorative compositions, paintings, furniture and kitchen utensils. Having mastered the basics of ancient art,some have dedicated their entire lives to it and become true masters of wood carving.